2017
DOI: 10.1002/uog.15866
|View full text |Cite
|
Sign up to set email alerts
|

Basic heart examination: feasibility study of first-trimester systematic simplified fetal echocardiography

Abstract: It is possible for a trained operator to perform simplified fetal echocardiography during the routine first-trimester ultrasound examination in a low-risk population. In most cases, our basic heart examination can be used to reassure parents or identify potential problems to be clarified as early as possible in the second trimester. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 23 publications
(35 reference statements)
1
54
0
2
Order By: Relevance
“…However, experienced operators using a combination of color Doppler assessment of the four chamber and three vessel and trachea view, a 89% sensitivity and 100% specificity was achieved (Wiechec et al, ). Similarly, Quarello et al investigated implementation of early fetal cardiac screening in a low‐risk setting (mainly utilizing transabdominal scanning) and found that the incorporation of the four‐chamber view and three vessel and trachea view with color or directional power Doppler during the routine first trimester ultrasound (between 11 + 0 and 13 + 6 weeks of gestation) yielded a sensitivity of 89% and specificity of 100% for detection of major congenital heart disease (Quarello, Lafouge, Fries, Salomon,, & CFEF, ). Following a brief training period, it was possible to obtain a satisfactory normal four chamber view in 86%, three vessel‐trachea view in 79% and both in 73% (Quarello et al, ).…”
Section: Screening the Fetal Heart In Early Pregnancymentioning
confidence: 99%
“…However, experienced operators using a combination of color Doppler assessment of the four chamber and three vessel and trachea view, a 89% sensitivity and 100% specificity was achieved (Wiechec et al, ). Similarly, Quarello et al investigated implementation of early fetal cardiac screening in a low‐risk setting (mainly utilizing transabdominal scanning) and found that the incorporation of the four‐chamber view and three vessel and trachea view with color or directional power Doppler during the routine first trimester ultrasound (between 11 + 0 and 13 + 6 weeks of gestation) yielded a sensitivity of 89% and specificity of 100% for detection of major congenital heart disease (Quarello, Lafouge, Fries, Salomon,, & CFEF, ). Following a brief training period, it was possible to obtain a satisfactory normal four chamber view in 86%, three vessel‐trachea view in 79% and both in 73% (Quarello et al, ).…”
Section: Screening the Fetal Heart In Early Pregnancymentioning
confidence: 99%
“…Previous studies have shown the feasibility of fetal heart assessment in low‐ or high‐risk pregnancies . We hypothesized that in obese women, fetal cardiac landmarks can be assessed with use of a standard technique during NT scan.…”
mentioning
confidence: 99%
“…Previous studies have shown the feasibility of fetal heart assessment in low-or high-risk pregnancies. 3,14 We hypothesized that in obese women, fetal cardiac landmarks can be assessed with use of a standard technique during NT scan. The purpose of this study was to show the feasibility of a standardized fetal heart examination in the evaluation of fetal cardiac landmarks in obese women around the time of NT scan.…”
mentioning
confidence: 99%
“…The combination of an NT > 95th percentile with an abnormal ductus venosus and/or tricuspid regurgitation can increase the detection rate for severe heart defects to > 50 % [28]. This marker screening for severe heart defects is increasingly being replaced by the integration of the four-chamber view and the three-vessel view into the detailed first-trimester examination [29,30].…”
Section: Early Diagnosis Of Anomaliesmentioning
confidence: 99%